A LOWER BOUND FOR THE LARGE SIEVE WITH SQUARE MODULI. Issue 2 (27th February 2019) - BAIER, STEPHAN; LYNCH, SEAN B.; ZHAO, LIANGYI
Abstract : We prove a lower bound for the large sieve with square moduli.